Estimation the levels of some heavy metals in the soil and vegetables irrigated with wells water in some agriculture fields at Al- Dora district – Baghdad - Mahmood , Mahmood Basil (Iraqi Journal of Science, 2022)
Heavy metals are currently of much environmental concern. The contamination by heavy metals in plants and water is one of the major issues to be faced throughout the world. This research is tried to estimate levels of heavy metals in vegetative crops and soil irrigated with well water (as alternative source for irrigation). Samples of well water, soil and vegetative crops were collected from agriculture fields at Al-Dora district in Baghdad. Physico-chemical parameters (pH, EC, TDS and Salinity) were measured for water and (pH, EC and salinity) for soil samples. Estimation of Lead (Pb), Nickle (Ni), Zinc (Zn) and Iron (Fe) concentrations in water, vegetable crops (Raphanus sativus, Apium graveoleus, Beta vulgaris, Allium ampeloprasum, Lepidium sativum, Eruca sativa and Petroselinum hortense) and soil samples were done. The results shows that the pH values ranged between 5.1- 6.4, EC 870-2760 μs/cm, TDS 430– 1390 mg/l and 0.5568- 1.7664 ppt for salinity of well water samples, while for soil samples the readings were 6.9-7.5, 200-1820 μs/cm and 0.128-1.1648 ppt for pH, EC and salinity, respectively. For heavy metals concentrations in wells water, the values were ranged between 1.636- 1.884 ppm, 1.068- 1.512 ppm, 0.292- 2.148 ppm and 1.404- 9.756 ppm for Pb, Ni, Zn and Fe, respectively. It was found that the samples of soil were contained Pb in the range 12.4- 58.2, Ni 144.5-214.83, Zn 83.07- 286.09 and Fe 16905.37- 22259.56 ppm, whereas the heavy metals concentrations in the vegetable crops were 0.92- 8.91, 11.78-82.82, 11.16- 77.44 and 628.44- 7977.07 ppm for Pb, Ni, Zn and Fe.